Control compounds for preclinical drug-induced liver injury assessment: Consensus-driven systematic review by the ProEuroDILI network - Segovia-Zafra, Antonio; Villanueva-Paz, Marina; Serras, Ana Sofía; Matilla-Cabello, Gonzalo; Bodoque-García, Ana; Di Zeo-Sánchez, Daniel Enrique; Niu, Hao; Álvarez-Álvarez, Ismael; Sanz-Villanueva, Laura; Godec, Sergej; Milisav, Irina; Bagnaninchi, Pierre; et al. (Elsevier, 2024)
Background & Aims Idiosyncratic drug-induced liver injury (DILI) is a complex and unpredictable event caused by drugs, and herbal or dietary supplements. Early identification of human hepatotoxicity at preclinical stages remains a major challenge, in which the selection of validated in vitro systems and test drugs has a significant impact. In this systematic review, we analyzed the compounds used in hepatotoxicity assays and established a list of DILI-positive and -negative control drugs for validation of in vitro models of DILI, supported by literature and clinical evidence and endorsed by an expert committee from the COST Action ProEuroDILI Network (CA17112). Methods Following 2020 PRISMA guidelines, original research articles focusing on DILI which used in vitro human models and performed at least one hepatotoxicity assay with positive and negative control compounds, were included. Bias of the studies was assessed by a modified ‘Toxicological Data Reliability Assessment Tool’. Results A total of 51 studies (out of 2,936) met the inclusion criteria, with 30 categorized as reliable without restrictions. Although there was a broad consensus on positive compounds, the selection of negative compounds lacked clarity. 2D monoculture, short exposure times and cytotoxicity endpoints were the most tested, although there was no consensus on drug concentrations. Conclusions Extensive analysis highlighted the lack of agreement on control compounds for in vitro DILI assessment. Following comprehensive in vitro and clinical data analysis together with input from the expert committee, an evidence-based consensus-driven list of 10 positive and negative control drugs for validation of in vitro models of DILI is proposed.
Keywords: Hígado - Enfermedades; Farmacología; Toxicidad - Ensayos in vitro; Medicamentos - Ensayos; Drug-induced liver injury; Preclinical drug safety testing; Validation of in vitro DILI models; Clinical data; Expert committee; Panel of control drugs; Control compounds